Design of subsystems for multiband wireless transceiver - Arjuna Marzuki (School of Microelectronic Engineering, 2010)
This thesis deals with the development of subsystems for wireless application. The subsystems are Low Noise Amplifier (LNA), Medium Power Amplifier (MPA), Demodulator, Variable Signal Generator (VSG) and Voltage for Current Source (VCS).